Gorham stout syndrome in maxilla and femur - Colaço, Jaqueline; Cesca, Henrique; Rovani, Gisele; Flores, Mateus Ericson; Conto, Ferdinando De (Journal of Oral Diagnosis, 2019)
Gorham Stout syndrome (SGS) is a rare disease that affects the bones causing idiopathic osteolysis. The prognosis of SGS is quite variable and impossible to predict, in most cases, bone destruction progresses from months to years, the affected area does not regenerate or repair itself. The etiology of the disease is unknown. The aim of the present study is to report a case in female patient showing a lesion in the left jaw compatible with the SGS. A 45-year-old female patient, was referred to the CTBMF team. After performing imaging tests to perform the differential diagnosis, they suggested as differential diagnosis of maxillary ossifying fibroma lesion and fibrous dysplasia, in relation to femoral lesion, was suggestive and enchondroma. The proposed treatment was surgical removal with curettage of the lesion in the femur and maxilla. With the result of the histopathological examination, the diagnosis of SGS was concluded. During the postoperative follow-up period, the lesion showed no signs of relapse, guaranteeing success in the treatment.